PERAN MEDIA SOSIAL, INFLUENCER, DAN KEBUDAYAAN MELALUI PERILAKU KONSUMTIF TERHADAP KEPUTUSAN PEMBELIAN MENGGUNAKAN VARIABEL INTERVENING PADA PRODUK BTS MEAL - Ismi Dwi Purwanti; Budi Istiyanto (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
This research aims to determine the relationship between social media, influencers, and culture on purchasing decisions through consumptive behavior as an intervening variable on BTS Meal products. In this research, social media, influencers, culture and consumptive behavior are aspects that influence BTS fans in buying BTS Meal products. The subjects in this research are BTS Meal fans who live in Solo Raya and are 15 to 50 years old with an unknown number. The sampling method used is the purposive sampling method using quantitative methods using the formula from Sugiyono, the number of samples is 96 people who are rounded up to 100 people with an error rate of 10%. The method of collecting information in this research uses a primary approach by distributing questionnaires. Information analysis was carried out using multiple linear regression with SPSS windows version boost. 26. Information analysis processed through SPSS includes data instrument testing (validity test and reliability test), classical assumption test (normality test, multicollinearity test, and heteroscedasticity test) and hypothesis testing (t test, F test, and R2 test).